Penguatan Deep Learning melalui Pendidikan Musik bagi Siswa Tunagrahita di SLB Negeri 3 Denpasar - I Komang Darmayuda; Yedija Remalya Sidjabat (Institut Seni Indonesia Denpasar, 2026)
Purpose: This study examines how educational management can be transformed to strengthen deep learning practices in inclusive school environments, particularly in the context of special education for students with intellectual disabilities. Using a qualitative descriptive research design, the study draws on observational, interview-based, and documentary evidence gathered from music-interactive learning sessions at SLB Negeri 3 Denpasar. The research aims to identify how structured, multisensory music activities can stimulate deep learning processes and how school-level management practices adapt to support such innovations. Method: Using a qualitative descriptive research design, the study draws on observational, interview-based, and documentary evidence gathered from music-interactive learning sessions at SLB Negeri 3 Denpasar. Result and Discussion: Results show that interactive music learning promotes sustained attention, emotional engagement, collaborative behavior, and intuitive pattern recognition among students with intellectual disabilities—indicating early markers of deep learning. Teachers also experienced a pedagogical shift, moving from passive supervision to active facilitation, demonstrating increased confidence and adaptive classroom management skills. Additionally, the school management exhibited incremental but meaningful transformations, including allocating consistent instructional time, reorganizing activity schedules, and providing more flexible learning spaces. Implication: These findings highlight that deep learning in inclusive settings does not depend solely on advanced technologies of Society 5.0 but can emerge through human-centered, experience-based pedagogical approaches such as music interaction. The study concludes that strengthening educational management through inclusive, creative, and multisensory learning environments can significantly enhance deep learning outcomes for students with intellectual disabilities. It also recommends broader institutional support for teacher capacity-building and the integration of arts-based strategies into inclusive education frameworks.